TEXTUAL SPACE OF THE PROFESSIONAL COMPETENCES - Irina V. Kuznetsova; Sergei S. Khmelev (Высшее образование в России)
The article marks the peculiarity of the competence model for graduates of applied and academic specialties. Metacharacteristics of teaching texts on Chemistry are defined. It is shown that in the situation when the systems of secondary school and higher education are misbalanced and labor market is multiple-optional, the training of the professional competences starts with students’ ability to work with different types of teaching texts.